2020
DOI: 10.1039/c9nr08714a
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicology at the particle/micelle frontier: influence of core-polymerization on the intracellular distribution, cytotoxicity and genotoxicity of polydiacetylene micelles

Abstract: Non-polymerized micelles accumulate in the cell membrane inducing permeabilization and high toxicity; polymerized, particle-like micelles are internalized but exert low toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…We observed similar phenomena as discussed above for the emission and absorption properties of SQN2@PMAOPEG at a mass ratio of 1/1000 (Figure e). Unfortunately, the amphiphilic molecules are known to be highly toxic and damage the cell membrane, and thus the dose of which should be carefully controlled . The MECPA effect ideally addressed the paradox of the PA efficiency and the cytotoxicity of the dye@micelle system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed similar phenomena as discussed above for the emission and absorption properties of SQN2@PMAOPEG at a mass ratio of 1/1000 (Figure e). Unfortunately, the amphiphilic molecules are known to be highly toxic and damage the cell membrane, and thus the dose of which should be carefully controlled . The MECPA effect ideally addressed the paradox of the PA efficiency and the cytotoxicity of the dye@micelle system.…”
Section: Resultsmentioning
confidence: 99%
“…Organic dyes are widely applied for in vivo PA and fluorescence imaging due to the relatively low cytotoxicity and great clinical translation potential. Nevertheless, as the absorption energy shifts to the NIR-II region, the photostability and absorption extinction coefficient would be a great challenge for organic dyes. , Furthermore, most of the recently developed NIR-II organic dyes exhibit poor solubility in aqueous solution, for instance, the NIR-II semiconducting polymers and cyanine derivative dyes (IR26, IR1061, and IR1048). ,, Therefore, the dye@micelle system is one of the most applied strategy for in vivo administration of PA contrast agents to improve the biocompatibility and prolong the blood circulation time. , In general, to retain the photophysical properties of dyes (such as absorbance), the mass ratio between dye and amphiphilic molecules was applied as largely as possible (mass ratio about 1:1000) . Unfortunately, the amphiphilic molecules are known to be highly toxic and damage the cell membrane, the amount of which should be carefully controlled for in vivo application (the lower, the better) . Therefore, the administration dose of the dye@micelle system would be compromised between the in vivo cytotoxicity tolerance (dose of amphiphilic molecules) and in vivo PA signal (dose of dye).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Recent work has demonstrated that PDAs with a higher degree of polymerization exhibit lower toxicity than partially polymerized PDA due to higher toxicity of DA monomers. 80,81 However, there have been no specific studies on the impact of contamination or addition of PDA in food. Recent investigations have focused on the toxicology of non-organic nanoparticles.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…hemolysis), therefore, the amount of which applied for in vivo study should be carefully controlled (the lower the better). 24 The administration amount of the dyes micelle system would be compromised between the in vivo tolerance of the cytotoxicity and in vivo PA signal. Furthermore, currently developed PA imaging contrast agents provide outstanding images of blood vessels, tumor tissue, etc.…”
Section: Introductionmentioning
confidence: 99%